ULTI-WAVELENGTH MONITORING OF THE CHANGING-LOOK AGN NGC 2617 DURING STATE CHANGES - Oknyansky, V. L.; Gaskell, C. M.; Huseynov, N. A.; Mikailov, Kh. M.; Lipunov, V. M.; Shatsky, N. I.; Tsygankov, S. S.; Gorbovskov, E. S.; Tatarnikov, A. M.; Metlov, V. G.; Malanchev, K. L.; Brotherton, M. B.; et al. (Одеські астрономічні публікації, 2017)
Optical and near-infrared photometry, optical spectroscopy, and soft X-ray and UV monitoring of the changing-look active galactic nucleus NGC 2617 show that it continues to have the appearance of a type-1 Seyfert galaxy. An optical light curve for 2010–2017 indicates that the change of type probably occurred between 2010 October and 2012 February and was not related to the brightening in 2013. In 2016 and 2017 NGC 2617 brightened again to a level of activity close to that in 2013 April. However, in 2017 from the end of the March to end of July 2017 it was in very low level and starting to change back to a Seyfert 1.8. We find variations in all passbands and in both the intensities and profiles of the broad Balmer lines. A new displaced emission peak has appeared in Hβ. X-ray variations are well correlated with UV–optical variability and possibly lead by 2–3 d. The K band lags the J band by about 21.5 ± 2.5 d and lags the combined B + J bands by 25 d. J lags B by about 3 d. This could be because J-band variability arises predominantly from the outer part of the accretion disc, while K-band variability is dominated by thermal re-emission by dust. We propose that spectral-type changes are a result of increasing central luminosity causing sublimation of the innermost dust in the hollow bi-conical outflow. We briefly discuss various other possible reasons that might explain the dramatic changes in NGC 2617.